Collective memory, memorialization and bearing witness in the aftermath of the Armenian Genocide - Marsoobian, Armen T. (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter describes and analyzes an ongoing project of memorialization of the Armenian Genocide in Turkey. It explores the importance of memorialization for collective historical memory, especially in situations where historical memory has been subverted by genocide denial. Among many aspects of memorialization, its role in bearing witness is explored and highlighted. Three components of the memory project are described: (1) the photography exhibitions, (2) the publications, and (3) the creation of memory sites. The project centers on the story of the Dildilian family in Ottoman Turkey before, during, and after the genocide, covering the years 1872–1923. A microhistory of the life of the Armenian minority is chronicled by means of the personal memories and stories of members of the family. The history is richly illustrated with photographs and drawings that serve as the basis of the photography exhibitions and books. Exhibitions and associated talks and panels have taken place in Istanbul, Merzifon, Diyarbakir, and Ankara. The chapter describes and analyzes the reaction of the Turkish public to the project.
Citation Key Alias: lens.org/145-690-138-443-429
Keywords: Armenian Genocide; Bearing witness; Collective memory; Genocide denial; Memorialization; Turkey; dept.phi